lead-acid batteries
Patent Information
- Application Number
- JP2025058841
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2026-10-14
AI Technical Summary
【0010】 本開示によれば、特に細孔径の大きなセパレータを用いる場合に、鉛蓄電池の深放電サイクル寿命性能が向上する。
Smart Images

Figure 2026166099000001_ABST
Abstract
Description
[Technical Field]
[0001] This disclosure relates to lead-acid batteries. [Background technology]
[0002] Patent Document 1 describes a lead-acid battery comprising a current collector, a positive electrode plate having a positive electrode material supported by the current collector, and a negative electrode plate, wherein the total pore volume per unit mass of the positive electrode material is 0.167 cm³. 3 The value is less than or equal to / g, and the positive electrode material contains fibers, and the average specific surface area of the fibers measured by the BET method using krypton gas as the adsorption gas is 0.25 m². 2 They are proposing a lead-acid battery that is rated at or above / g.
[0003] Patent Document 2 proposes a separator for a lead-acid battery comprising a polyolefin microporous membrane, wherein the polyolefin microporous membrane comprises polyethylene, preferably ultra-high molecular weight polyethylene, a particulate filler, and a treatment plasticizer, wherein the particulate filler is present in an amount of 40% or more by weight, and the polyethylene comprises a shish-kebab forming polymer including a plurality of elongated chain crystals (shishi formation) and a plurality of folded chain crystals (kebab formation), wherein the average repetition or period of the kebab formation is from 1 nm to 150 nm, preferably less than 120 nm. [Prior art documents] [Patent Documents]
[0004] [Patent Document 1] Japanese Patent Publication No. 2019-67741 [Patent Document 2] Special Publication No. 2019-514173 [Overview of the project] [Problems that the invention aims to solve]
[0005] In recent years, with the advent of vehicles controlled by idling stop-start (ISS) and OTA (Over The Air) technology, the load borne by lead-acid batteries has been increasing more and more. When charge-discharge cycles with a deep discharge depth (hereinafter also referred to as "deep discharge cycles") are repeated, softening and falling off of the positive electrode material of the lead-acid battery are prone to occur, so it is necessary to improve the durability of the positive electrode material.
[0006] In order to improve the durability of the positive electrode material, it has been proposed to add fibers to the positive electrode material (Patent Document 1).
[0007] Further, there has been proposed a separator with improved ion diffusivity and reduced resistance by, for example, increasing the pore size of a polyolefin microporous separator or reducing the tortuosity of pores (Patent Document 2).
[0008] However, as the pore size of the separator increases, the fallen positive electrode material easily penetrates into the inside of the separator, and a short circuit due to the fallen positive electrode material is likely to occur. As a result, it becomes difficult to improve the life performance of the lead-acid battery. [Means for Solving the Problems]
[0009] One aspect of the present disclosure includes a positive electrode plate, a negative electrode plate, an electrolytic solution, and a separator interposed between the positive electrode plate and the negative electrode plate, wherein the positive electrode plate includes a positive electrode current collector and a positive electrode material, the positive electrode material includes fibers, and the fibers have a BET specific surface area measured using krypton gas as an adsorption gas of 0.3 m 2 / g or more and 1.0 m 2 / g or less, and in the pore size distribution of the separator, the cumulative pore volume V1 of pore sizes from 0.005 μm to 10 μm is 0.8 cm 3 / g or more and 2.0 cm 3 / g or less, and the ratio r1 of the pore volume V2 of pore sizes of 0.1 μm or more and 10 μm or less to the cumulative pore volume V1 is 50% or more, relating to a lead-acid battery. [Effects of the Invention]
[0010] According to the present disclosure, the deep discharge cycle life performance of a lead-acid battery is improved particularly when a separator having a large pore size is used. [Brief Description of the Drawings]
[0011] [Figure 1] This is a partially cutaway perspective view showing the external appearance and internal structure of a lead-acid battery according to one embodiment of the present invention. [Modes for Carrying Out the Invention]
[0012] Hereinafter, the embodiments of the present disclosure will be described with examples, but the present disclosure is not limited to the examples described below. In the following description, specific numerical values and materials may be exemplified, but other numerical values and materials may be applied as long as the effects of the present disclosure can be obtained. In this specification, the description "numerical value A to numerical value B" includes numerical value A and numerical value B, and can be read as "not less than numerical value A and not more than numerical value B". In the following description, when the lower limit and upper limit of numerical values relating to specific physical properties, conditions, etc. are exemplified, any one of the exemplified lower limits and any one of the exemplified upper limits can be arbitrarily combined as long as the lower limit does not exceed the upper limit. When a plurality of materials are exemplified, one type may be selected and used alone, or two or more types may be used in combination.
[0013] Furthermore, the present disclosure encompasses combinations of the matters described in two or more claims arbitrarily selected from the plurality of claims described in the appended claims. That is, as long as no technical contradiction arises, the matters described in two or more claims arbitrarily selected from the plurality of claims described in the appended claims can be combined.
[0014] (1) The lead-acid battery according to the present embodiment (hereinafter also referred to as "lead-acid battery (B)") includes a positive electrode plate, a negative electrode plate, an electrolytic solution, and a separator interposed between the positive electrode plate and the negative electrode plate, and the positive electrode plate includes a positive electrode current collector and a positive electrode material. The positive electrode material contains fibers. The fibers have a BET specific surface area measured using krypton gas as an adsorption gas of 0.3 m2 / g or more and 1.0 m 2 / g or less. In the pore size distribution of the separator, the cumulative pore volume V1 of pore sizes of 0.005 μm to 10 μm is 0.8 cm 3 / g or more and 2.0 cm 3 / g or less, and the ratio r1 (=V2 / V1) of the pore volume V2 of pore sizes of 0.1 μm to 10 μm occupying the cumulative pore volume V1 is 50% or more. Hereinafter, the separator having the above pore size distribution is also referred to as "separator (SS)". 2 6>
[0015] The pore size distribution of the separator (SS) is determined by a mercury intrusion porosimetry method. The ratio r1 is the ratio of the total sum of the volumes of pores having pore sizes of 0.1 μm to 10 μm to the total sum of the volumes of pores having pore sizes of 0.005 μm to 10 μm in the pore size distribution determined by the mercury intrusion porosimetry method.
[0016] The separator (SS) has a large number of pores with pore sizes in the range of 0.1 μm to 10 μm, and has high electrolyte diffusivity (ion diffusivity). Thereby, the resistance of the separator (SS) can be kept low, and high-rate discharge performance (HR discharge performance) is improved.
[0017] On the other hand, a lead-acid battery using the separator (SS) has many pores with large pore sizes, so that as charge-discharge cycles are repeated, the softened or fallen-off positive electrode active material clogs the pores, and short circuits caused by the fallen-off positive electrode active material penetrating through the pores tend to occur. As a result, as charge-discharge cycles are repeated, the lead-acid battery reaches the end of its service life due to a short circuit caused by the positive electrode active material that has fallen off into the separator, and tends to have a short service life.
[0018] In the lead-acid battery (B) described in the above (1), the binding force between the positive electrode active materials is significantly enhanced by the fibers. Therefore, high binding properties with the electrode material particles coarsened by charge and discharge can be maintained, and falling off can be suppressed via van der Waals forces between the fibers and the positive electrode active material particles.
[0019] In the charged state, the positive electrode material forms a network of bonded lead dioxide particles. When the discharge reaction changes the lead dioxide to lead sulfate, its volume expands by approximately 1.5 times. Repeated deep discharge cycles typically cause the bonds between lead compound particles in the positive electrode material to break, isolating some of the lead compounds. As a result, softening progresses from the surface of the positive electrode plate, leading to the detachment of the positive electrode material. To suppress such softening and detachment, it is considered necessary that the contact area between the fibers contained in the positive electrode material and the positive electrode material itself be sufficiently large.
[0020] BET specific surface area is 0.3m 2 / g or more 1.0m 2 Fibers with a lead content of less than / g have a very large specific surface area, resulting in a very large contact area between the fiber and the lead compound. The large contact area allows the fiber and lead compound to intertwine, increasing the binding force between the lead compounds, which suppresses softening and detachment of the positive electrode material and enables a long lifespan. In addition, because the separator (SS) has low resistance, the charge-discharge reaction proceeds smoothly, making localized degradation of the positive electrode material less likely. Specifically, if the separator's resistance is high and the charge-discharge reaction does not proceed smoothly, the charge-discharge reaction will not proceed smoothly in the lower part of the electrode plate, far from the lugs, and the load from the charge-discharge reaction will concentrate in the upper part of the electrode plate, making localized degradation more likely in the upper part of the electrode plate. On the other hand, if the separator's resistance is low and the charge-discharge reaction proceeds smoothly, the charge-discharge reaction will also proceed smoothly in the lower part of the electrode plate, making localized degradation in the upper part of the electrode plate less likely. Furthermore, since the load from the charge-discharge reaction is more easily distributed across the entire electrode plate, the degree of degradation of the entire electrode plate is smaller compared to localized degradation. In other words, when fibers with a very large contact area with lead compounds and a separator (SS) are used simultaneously, the bonding strength between lead compounds is enhanced on the electrode plate, which is less prone to localized degradation, making it easier to maintain the bonding strength between lead compounds. As a result, it becomes possible to achieve both a long lifespan and high HR discharge performance.
[0021] (2) In the lead-acid battery (B) described in (1) above, the fiber content in the positive electrode material is preferably 0.01% by mass to 0.23% by mass.
[0022] By including 0.01% by mass or more of fibers having a specific surface area within the above range in the positive electrode material, a sufficient effect can be obtained to suppress softening and shedding of the positive electrode material. On the other hand, the higher the fiber content or the larger the specific surface area of the fibers, the lower the conductivity of the positive electrode material (the higher the resistance), and the more likely the HR discharge performance is to decrease. By setting the fiber content to 0.23% by mass or less, a long life can be achieved without causing a significant decrease in HR performance when using fibers having a specific surface area within the above range. The fiber content may be 0.01% by mass or more and 0.23% by mass or less, and more preferably 0.07% by mass or more and 0.20% by mass or less.
[0023] (3) In the lead-acid battery (B) described in (1) or (2) above, the average fiber diameter of the fibers is preferably 10 μm or less.
[0024] Based on the finding that the thinner the fiber diameter, the larger the contact area between the lead compound constituting the positive electrode material and the fiber, and the greater the effect of suppressing softening and detachment of the positive electrode material by the fiber, when the average fiber diameter of the fiber in the lead-acid battery (B) described in (1) or (2) above is made thinner to 10 μm or less, the fiber has a large specific surface area, so the contact area between the lead compound constituting the positive electrode material and the fiber increases. As a result, the effect of improving the bonding strength between the positive electrode materials by the fiber increases.
[0025] In the lead-acid battery (B) described in (1) or (2) above, the average fiber diameter of the fibers may be 9 μm or less. From the viewpoint of ensuring sufficient strength of the fibers themselves, the average fiber diameter of the fibers is preferably 0.1 μm or more, and may also be 0.5 μm or more. The average fiber diameter of the fibers can be controlled during the fiber synthesis process.
[0026] (4) In the lead-acid battery (B) described in any one of (1) to (3) above, the average fiber diameter is preferably 1 μm to 8 μm.
[0027] In the lead-acid battery (B) described in any one of (1) to (3) above, if the average fiber diameter of the fibers is in the range of 1 μm to 8 μm, the fibers have a larger specific surface area, thus increasing the contact area between the lead compound constituting the positive electrode material and the fibers. Furthermore, by making the average fiber diameter of the fibers 1 μm or more, higher strength of the fibers can be ensured. This further enhances the effect of the fibers on improving the bonding strength between the positive electrode materials.
[0028] In the lead-acid battery (B) described in any one of (1) to (3) above, the average fiber diameter of the fibers may be in the range of 0.1 μm to 16 μm, 0.5 μm to 12 μm, 1 μm to 8 μm, 2 μm to 8 μm, or 3 μm to 10 μm.
[0029] (5) In the lead-acid battery (B) described in any one of (1) to (4) above, it is preferable that the surface of the fiber has irregularities. Furthermore, it is preferable that the irregularities on the surface of the fiber are formed along the circumferential direction of the fiber. The circumferential direction of the fiber is any direction that intersects the longitudinal direction of the fiber. Such a direction is, for example, a direction that has an angle of 45° or more on average with the longitudinal direction of the fiber.
[0030] In the lead-acid battery (B) described in (5) above, the friction between the lead compound particles and the fibers is increased by the surface irregularities of the fibers. In particular, when the surface irregularities of the fibers are formed along the circumferential direction of the fibers, the friction is greater when the lead compound particles try to move in the longitudinal direction of the fibers. Therefore, an effect is obtained in which the expansion of the positive electrode material along the longitudinal direction of the fibers is suppressed.
[0031] In the lead-acid battery (B) described in (5) above, the surface irregularities of the fibers may be formed in a ripple-like pattern along the circumferential direction of the fibers. The trajectory of the ripple-like irregularities extending on the surface of the fibers is long, and the shape of the irregularities is complex. Therefore, such irregularities are likely to engage with particles of the lead compound that are trying to move in the longitudinal direction of the fibers. Thus, the effect of suppressing the expansion of the positive electrode material along the longitudinal direction of the fibers is further enhanced.
[0032] The irregularities may be formed on the fibers beforehand, or they may be formed on smooth fibers by a predetermined method, or they may be formed during the manufacturing process of the lead-acid battery. One method for forming irregularities on the surface of fibers is chemical treatment, which modifies the fiber surface using chemicals such as acids and alkalis. Other methods for forming irregularities on the surface of fibers include plasma treatment, which modifies the fiber surface using plasma, corona treatment, which modifies the fiber surface using high-voltage discharge, and UV irradiation treatment, which modifies the fiber surface using ultraviolet light. Yet another method is sandblasting, for example. Sandblasting is a process in which fine powder harder than the fiber is impacted onto the fiber.
[0033] When using methods such as plasma treatment, corona treatment, or UV irradiation to create irregularities on fibers, the state of the irregularities may be altered by changing the output value of the processing device, the processing time, or both. In sandblasting, the speed of the fine powder impacting the fibers and the processing time can also be changed.
[0034] The lead-acid battery (B) relating to this disclosure may be a valve-regulated lead-acid battery (VRLA type battery) or a liquid-type battery (vented type battery).
[0035] A lead-acid battery (B) comprises a positive electrode plate, a negative electrode plate, a separator interposed between the positive and negative electrode plates, and an electrolyte. The electrolyte contains sulfuric acid. Charging and discharging proceed through the movement of sulfate ions between the positive and negative electrode plates and the electrolyte.
[0036] A positive electrode plate, a negative electrode plate, and a separator constitute an electrode group. The electrode group, together with the electrolyte, constitutes a cell. One electrode group constitutes one cell. A lead-acid battery (B) comprises one or more cells by comprising one or more electrode groups. There is no particular limit to the number of positive and negative electrode plates included in one electrode group. An electrode group comprising a lead-acid battery (B) according to this disclosure may include, for example, a total of 12 or more positive and negative electrode plates. Multiple electrode groups are usually housed in separate cell chambers and connected in series with one another.
[0037] The negative electrode plate includes a negative electrode current collector and a negative electrode material. The negative electrode material is a negative electrode active material that exhibits capacity through an oxidation-reduction reaction, and contains at least lead during charging and at least lead sulfate during discharging.
[0038] The positive electrode plate includes a positive electrode current collector and a positive electrode material. The positive electrode material is a positive electrode active material that exhibits capacity through oxidation-reduction reactions, and contains at least lead dioxide during charging and at least lead sulfate during discharge.
[0039] In this specification, the fully charged state of a liquid lead-acid battery is defined according to the definition in JIS D5301:2019. More specifically, in a water bath at 25°C ± 2°C, the 20-hour rate current I is charged until the terminal voltage (in volts) or the electrolyte density converted to 20°C shows a constant value with three significant figures for three consecutive 15-minute intervals. 20 Twice the current 2I 20 (Unit: A) The fully charged state of a lead-acid battery is defined as the state in which it has been charged. Note that the 20-hour rate current I 20 This refers to a current (A) that is 1 / 20th of the Ah value listed in the rated capacity. The value listed as the rated capacity is a value in Ah (ampere-hour). The unit of the current set based on the value listed as the rated capacity is A (ampere).
[0040] Furthermore, in the case of a valve-regulated lead-acid battery, a fully charged state is defined as a 20-hour rate current of 1 in an air chamber at 25°C ± 2°C. 20 5 times the current 5I 20 The battery was then charged at a constant current and voltage of 2.67V / cell (16.00V for a lead-acid battery with a nominal voltage of 12V), and the charging process was terminated when the total charging time reached 24 hours.
[0041] A fully charged lead-acid battery is a lead-acid battery that has been charged to its full capacity after chemical formation. The timing for charging a lead-acid battery to its full capacity can be immediately after chemical formation, or after a certain amount of time has passed since formation (e.g., 720 hours or less). For example, a lead-acid battery that has been chemically formed and is in use (preferably in the early stages of use) may be charged.
[0042] In this specification, a battery in its initial use refers to a battery that has not been used for very long and has not deteriorated much (for example, a battery that has been in use for less than 720 hours, including the time elapsed since chemical preparation).
[0043] The lead-acid battery (B) according to an embodiment of the present invention will be described in more detail below with reference to the drawings. However, the present invention is not limited to the following embodiments.
[0044] The following describes examples of components of a lead-acid battery (B).
[0045] Figure 1 shows the external appearance and part of the internal structure of a lead-acid battery 1 according to one embodiment. The lead-acid battery 1 comprises a battery case 12 that houses an electrode plate group 11 and an electrolyte (not shown). The inside of the battery case 12 is divided into a plurality of cell chambers 14 by a partition wall 13. Each cell chamber 14 houses one electrode plate group 11. The opening of the battery case 12 is closed with a lid 15 equipped with a negative electrode terminal 16 and a positive electrode terminal 17. The lid 15 is provided with a vent plug 18 for each cell chamber. When replenishing water, the vent plug 18 is removed and the water is supplied. The vent plug 18 may also have a function of discharging gas generated in the cell chamber 14 to the outside of the battery.
[0046] Each electrode plate group 11 is constructed by stacking multiple negative electrode plates 2 and positive electrode plates 3 via separators 4. The separators 4 are separators (SS) whose pore size distribution satisfies the above relationship. Here, a bag-shaped separator 4 that houses the negative electrode plates 2 is shown, but the form of the separator other than the pore size distribution is not particularly limited. In the cell chamber 14 located at one end of the battery case 12, a negative electrode shelf 6 connecting multiple negative electrode plates 2 in parallel is connected to a through-connector 8, and a positive electrode shelf 5 connecting multiple positive electrode plates 3 in parallel is connected to a positive electrode column 7. The positive electrode column 7 is connected to a positive electrode terminal 17 on the outside of the lid 15. In the cell chamber 14 located at the other end of the battery case 12, a negative electrode column 9 is connected to the negative electrode shelf 6, and a through-connector 8 is connected to the positive electrode shelf 5. The negative electrode column 9 is connected to a negative electrode terminal 16 on the outside of the lid 15. Each through-connector 8 passes through a through-hole provided in the partition wall 13, connecting the electrode plate groups 11 of adjacent cell chambers 14 in series.
[0047] Note that Figure 1 is merely an example of a liquid-type lead-acid battery, and the structure of the lead-acid battery (B) according to this disclosure is not limited to the example shown in the figure. Furthermore, the following description does not limit the configuration of the lead-acid battery (B) according to the present invention.
[0048] (Negative electrode plate) The negative electrode plate of a lead-acid battery (B) consists of a negative electrode current collector and a negative electrode material. The negative electrode material is the portion of the negative electrode plate excluding the negative electrode current collector. In some cases, an adhesive member may be attached to the negative electrode plate. In this case, the adhesive member is included in the negative electrode plate. When the negative electrode plate includes an adhesive member, the negative electrode material is the portion of the negative electrode plate excluding the negative electrode current collector and the adhesive member.
[0049] The negative electrode current collector included in the negative electrode plate may be formed by casting lead (Pb) or lead alloy (NA), or by processing a lead or lead alloy sheet. Examples of processing methods include expanding or punching. Using a grid-shaped current collector as the negative electrode current collector is preferable because it makes it easier to support the negative electrode material.
[0050] The lead alloy used for the negative electrode current collector may be any of the following: lead alloy (NA), Pb-Sb alloy, Pb-Ca alloy, or Pb-Ca-Sn alloy. The lead alloy (NA) may also be an alloy containing antimony (Sb), aluminum (Al), sodium (Na), silver (Ag), etc. The negative electrode current collector may have lead alloy layers of different compositions, and the alloy layer may be a single layer or multiple layers.
[0051] The negative electrode material contained in the negative electrode plate contains Pb. Pb is a negative electrode active material that exhibits capacity through oxidation-reduction reactions and is included in the negative electrode material as lead or lead sulfate.
[0052] The negative electrode material may further contain organic shrinkage inhibitors, carbonaceous materials, barium sulfate, reinforcing materials, and the like.
[0053] Examples of organic shrinkage inhibitors include lignin, lignin sulfonic acid, and synthetic organic shrinkage inhibitors (such as formaldehyde condensates of phenolic compounds). The content of the organic shrinkage inhibitor in the negative electrode material is, for example, 0.01% by mass or more. The content of the organic shrinkage inhibitor is, for example, 1.2% by mass or less.
[0054] Examples of carbonaceous materials include carbon black, graphite, hard carbon, and soft carbon. The carbonaceous material content in the negative electrode material is, for example, 0.1% by mass or more. The carbonaceous material content may also be, for example, 3.5% by mass or less.
[0055] The barium sulfate content in the negative electrode material is, for example, 0.1% by mass or more and 3% by mass or less.
[0056] Examples of reinforcing materials include fibers (inorganic fibers, organic fibers, etc.). The reinforcing material content in the negative electrode material is, for example, 0.03% by mass or more. Alternatively, the reinforcing material content in the negative electrode material is, for example, 0.6% by mass or less.
[0057] The negative electrode plate can be formed by filling a negative electrode current collector with negative electrode paste, aging and drying it to produce an unformed negative electrode plate, and then forming the unformed negative electrode plate. The negative electrode paste is made by kneading lead powder, an organic shrinkage inhibitor, barium sulfate, etc., with water and sulfuric acid. The negative electrode active material in the charged state is spongy lead, but the unformed negative electrode plate is usually made using lead powder. In the aging process, it is preferable to age the unformed negative electrode plate at a temperature higher than room temperature and at high humidity.
[0058] The chemical conversion can be carried out by immersing the electrode plate group, including the unconverted negative electrode plate, in the sulfuric acid-containing electrolyte in the lead-acid battery (B) case and then charging the electrode plate group. However, the chemical conversion may also be carried out before the assembly of the lead-acid battery (B) or the electrode plate group. Spongy lead is produced by the chemical conversion.
[0059] (Positive plate) For example, a paste-type positive electrode plate is used as the positive electrode plate. A paste-type positive electrode plate comprises a positive electrode current collector and a positive electrode material. The positive electrode material is held by the positive electrode current collector. The positive electrode material is the portion of the positive electrode plate excluding the positive electrode current collector. In addition, materials such as mats and pasting paper may be attached to the positive electrode plate. Since such attached materials are used integrally with the positive electrode plate, they are included in the positive electrode plate. When the positive electrode plate includes attached materials, the positive electrode material is the portion of the positive electrode plate excluding the positive electrode current collector and attached materials.
[0060] The positive electrode current collector included in the positive electrode plate may be formed by casting lead (Pb) or a lead alloy, or by processing a lead or lead alloy sheet. Examples of processing methods include expanding or punching. Using a grid-shaped current collector as the positive electrode current collector is preferable because it makes it easier to support the positive electrode material.
[0061] The lead alloy used for the positive electrode current collector may be an alloy containing antimony (Sb), aluminum (Al), sodium (Na), silver (Ag), etc. The positive electrode current collector may have lead alloy layers with different compositions, and the alloy layer may be a single layer or multiple layers.
[0062] The positive electrode material contained in the positive electrode plate includes a positive electrode active material (lead dioxide or lead sulfate) that exhibits capacity through oxidation-reduction reactions, and contains fibers as an additive. The positive electrode material may also contain other additives as needed.
[0063] The fiber content in the positive electrode material may be, for example, 0.005% by mass or more and 0.25% by mass or less, 0.01% by mass or more and 0.23% by mass or less, 0.02% by mass or more and 0.23% by mass or less, 0.02% by mass or more and 0.20% by mass or less, 0.07% by mass or more and 0.20% by mass or less, or 0.14% by mass or more and 0.20% by mass or less.
[0064] The BET specific surface area of the fibers in the positive electrode material is 0.3 m². 2 / g or more 1.0m 2 It is less than / g. By using such fibers, the shedding of the positive electrode material is suppressed, and by using a separator (SS) with appropriately controlled pore size distribution, it becomes possible to achieve both long life and high HR discharge performance. In contrast, the BET specific surface area is 0.3m². 2 Even when using fibers with a density of less than 0.3 m² / g, the above effects cannot be obtained at all when using a separator (SS). In other words, the BET specific surface area of the fibers used in the positive electrode material is 0.3 m². 2 If the value is 0.3m or more, 2 The behavior of the lifetime performance due to the shedding of the positive electrode material, which is caused by the pore size distribution of the separator being within a specific range, is completely different when the value is less than / g. Here, the BET specific surface area is determined using the BET formula by a gas adsorption method with krypton gas as the adsorbing gas.
[0065] From the viewpoint of ease of manufacturing the positive electrode plate, the BET specific surface area is 1.0 m². 2It is less than / g and 0.6m 2 / g or less or 0.5m 2 It may be less than / g.
[0066] The effect of suppressing softening and shedding by fibers can also depend on the material of the fibers. Preferably, the fibers are made of a resin that is thin yet strong and stable in the presence of sulfuric acid.
[0067] As the fibers, inorganic fibers or organic fibers may be used, or both inorganic and organic fibers may be used. From the viewpoint of easily controlling the BET specific surface area, organic fibers are preferred. Examples of resins (or polymers) that constitute the organic fibers include acrylic resins, polyolefin resins (polypropylene resins, polyethylene resins, etc.), polyester resins (including polyalkylene arylates (polyethylene terephthalate, etc.)), and celluloses (cellulose, cellulose derivatives (cellulose ethers, cellulose esters, etc.)). Rayon is also included in the celluloses.
[0068] The resin constituting the fiber may be at least one selected from the group consisting of polyester and polyolefin, as it has excellent acid or alkali resistance. Examples of polyester include polyalkylene arylates such as polyethylene terephthalate (PET) and polybutylene terephthalate (PBT). Examples of polyolefins include polyethylene, polypropylene (PP), and ethylene-propylene copolymer. Among these, PET has excellent acid resistance and mechanical strength. Therefore, fibers made of PET have a fine average fiber diameter and can secure a large surface area even in small quantities, making it easy to improve the deep discharge life of lead-acid batteries (B). Furthermore, PET fibers are inexpensive.
[0069] For example, 85% or more of the fiber may be composed of polyester. Fibers containing such a high percentage of polyester are usually called polyester fibers (e.g., PET fibers). Also, 85% or more of the fiber may be composed of polyolefin. Fibers containing such a high percentage of polyolefin are usually called polyolefin fibers (e.g., polyethylene fibers, polypropylene fibers). Similarly, fibers in which 85% or more of the fiber is composed of acrylic resin are called acrylic fibers.
[0070] The fibers may contain one type of resin, or two or more types. Furthermore, the positive electrode material may contain multiple fibers formed from different resins. Among these resins, using an acrylic resin makes it easier to form fine wrinkles on the fiber surface, thus making it easier to control the BET specific surface area within a desired range.
[0071] The manufacturing method of the fibers contained in the positive electrode material is not particularly limited, as long as the BET specific surface area is within the above range. The fibers may be formed, for example, by wet spinning. In wet spinning, fibers can be formed by spinning a solution (spinning stock) in which a resin is dissolved in a solvent into a liquid coagulation solution. At this time, the diffusivity of the solvent from the coagulated product of the spinning stock, which has solidified in the coagulation solution, can be adjusted by selecting the solvent used in the spinning stock and the composition of the coagulation solution. This adjusts the degree of volume reduction in the coagulation product, making it easier to form fine wrinkles on the surface of the fibers. In this way, the BET specific surface area can be adjusted.
[0072] The type of resin constituting the fibers contained in the positive electrode material can be identified by analyzing the fibers recovered from the positive electrode material using the method described in JIS L 1030-1:2012. The fibers may be recovered by pulling them out of the positive electrode material with tweezers, or they may be recovered from the residue after dissolving the lead compound contained in the positive electrode material, as described below.
[0073] The positive electrode material is recovered from the positive electrode plate by the following procedure. First, a fully charged lead-acid battery is disassembled, and the obtained positive electrode plate is washed with water for 3 to 4 hours to remove the electrolyte from the positive electrode plate. The washed positive electrode plate is dried in a constant temperature bath at 60°C ± 5°C for 5 hours or more. After drying, if the positive electrode plate contains adhesive material, the adhesive material is removed from the positive electrode plate by peeling. The fibers contained in the adhesive material are not included in the fibers of the present invention. If adhesive material was attached to the positive electrode plate, the surface of the positive electrode plate is scraped to a depth of 0.03 mm to 0.20 mm until the residue of the adhesive material is removed. Then, a sample of the positive electrode material for analysis is obtained by taking a sample of the positive electrode material from near the center when the positive electrode plate is viewed from the front, without crushing it.
[0074] The fibers are recovered from the positive electrode material sample by the following procedure. First, a predetermined amount Wg (e.g., about 70g) of positive electrode material sample is crushed and accurately weighed. At this time, the positive electrode material contained in one or more positive electrode plates may be used as the sample.
[0075] Next, the pulverized sample is added to a mixed solution of acetic acid-sodium acetate solution and sodium thiosulfate solution (acetic acid concentration 1.7 mol / L, sodium acetate concentration 6.1 mol / L, sodium thiosulfate concentration 0.5 mol / L), and the soluble components are dissolved while stirring at room temperature. The resulting residue is then filtered using a membrane filter (average pore size: 0.45 μm or less). The filter is washed with deionized water during filtration. This allows the fibers contained in the positive electrode material to be obtained as solid matter on the filter paper.
[0076] A fiber sample for analysis is obtained by washing and drying the resulting solid. The mass w of the fiber sample is measured. The percentage of the mass w of the fiber sample relative to the mass W of the positive electrode material sample is the fiber content in the positive electrode material.
[0077] Using a fiber sample, the BET specific surface area is determined using the following apparatus under the following conditions. Measuring device: Shimadzu Corporation, TriStar II 3020 series Adsorption gas: Krypton gas with a purity of 99.99% or higher. Adsorption temperature: -196℃ Method for calculating BET specific surface area: Conforms to JIS Z 8830:2013, section 7.2.
[0078] The resin constituting the fibers can be identified by analyzing the infrared absorption spectrum of the fiber sample. Method B (film method) specified in JIS L 1030-1:2024 may be used as the analytical method.
[0079] Specifically, the fiber sample is dissolved in an appropriate dissolving reagent (see Table A), poured into an evaporating dish, and dried under vacuum or by heating to a temperature that does not decompose the sample. Next, the dried film is peeled off without tearing, cut to an appropriate size, and the infrared absorption spectrum is measured in accordance with JIS K 0117:2017. The film should be of a thickness that makes it transparent. Also, the size of the film will vary depending on the infrared spectrophotometer used, so it should be at least 1 cm. 2 That concludes this section.
[0080] Table A exemplifies the main absorption bands and characteristic wavenumbers of the infrared absorption spectra of various fibers, as well as the dissolving reagents. The absorption bands and characteristic wavenumbers of each fiber vary by ±20 cm depending on the infrared spectrophotometer used. -1 There are differences in degree.
[0081] [Table A]
[0082] The average fiber diameter D of a fiber is determined by selecting any 20 fibers from a fiber sample, measuring the fiber diameter (the dimension perpendicular to the length of the fiber) at any point on each fiber, and taking the arithmetic mean of the measurements. The average fiber diameter D of a fiber may also be measured using a scanning electron microscope (SEM) image of the fiber.
[0083] Unformed paste-type positive electrode plates are obtained by filling a positive electrode current collector with positive electrode paste, followed by maturation and drying. The positive electrode paste is prepared by kneading lead powder, and optionally additives (such as reinforcing materials), with water and sulfuric acid.
[0084] A positive electrode plate can be obtained by chemically treating an untreated positive electrode plate. Chemical treatment can be carried out by immersing the electrode plate group, including the untreated positive electrode plate, in an electrolyte containing sulfuric acid in the battery case of a lead-acid battery (B), and then charging the electrode plate group. However, chemical treatment may also be carried out before the assembly of the lead-acid battery (B) or the electrode plate group.
[0085] (Separator) As the separator (SS) placed between the negative electrode and the positive electrode, at least one selected from, for example, nonwoven fabric and microporous membrane can be used. The material of the separator (SS) is not particularly limited as long as it has a pore size distribution and ratio r1 within the above range.
[0086] Nonwoven fabrics are mats composed of interwoven fibers rather than woven fibers, and are primarily fiber-based. For example, 60% or more of the nonwoven fabric is made up of fibers. Suitable fibers include glass fibers, polymer fibers (polyolefin fibers, acrylic fibers, polyester fibers (such as polyethylene terephthalate fibers), etc.), and pulp fibers. Glass fibers are preferred among these. Nonwoven fabrics may also contain other components besides fibers, such as acid-resistant inorganic powders and polymers as binders.
[0087] A microporous membrane is a porous sheet mainly composed of non-fibrous components. For example, it can be obtained by extruding a composition containing a pore-forming agent into a sheet, and then removing the pore-forming agent to form pores. Microporous membranes are preferably composed of acid-resistant materials, and preferably mainly composed of polymer components. Polyolefins (such as polyethylene and polypropylene) are preferred as polymer components. Examples of pore-forming agents include polymer powders and oils.
[0088] The separator may consist solely of a nonwoven fabric, or solely of a microporous membrane. The separator may also be a laminate of a nonwoven fabric and a microporous membrane, a laminate of different or the same type of material bonded together, or a laminate of different or the same type of material with interlocking protrusions and indentations.
[0089] The separator may be in the form of a sheet or a bag. A single sheet-shaped separator may be placed between the positive and negative electrodes. The electrode plates may be sandwiched between folded sheet-shaped separators. The positive electrode sandwiched between folded sheet-shaped separators and the negative electrode sandwiched between folded sheet-shaped separators may be stacked on top of each other, or one of the positive and negative electrodes may be sandwiched between folded sheet-shaped separators and stacked on top of the other electrode plate. When a bag-shaped separator is used, the bag-shaped separator may contain either the positive electrode or the negative electrode.
[0090] The separator may or may not have ribs. A separator with ribs, for example, comprises a base portion and ribs erected from the surface of the base portion. The ribs may be provided on only one surface of the separator or each base portion, or on both surfaces. The base portion of the separator refers to the part of the separator's components excluding protrusions such as ribs, and is a sheet-like portion that defines the outer shape of the separator.
[0091] As mentioned above, in the pore size distribution of the separator (SS), the cumulative pore volume V1 for pore sizes from 0.005 μm to 10 μm is 0.8 cm³. 3 / g or more 2.0cm 3 The ratio of pore volume V2 with a pore diameter of 0.1 μm to 10 μm to the total pore volume V1 is r1 (=V2 / V1) of 50% or more. Having a ratio r1 within this range allows for high diffusivity of the electrolyte and keeps the separator resistance low.
[0092] The ratio r1 is 50% or more, and may be 60% or more. For example, the ratio r1 is 70% or less. The ratio r1 may be 50% or more and 70% or less, or 50% or more and 60% or less.
[0093] The cumulative pore volume V1 is 0.8 cm³. 3 / g or more 2.0cm 3 It is less than / g and 1.0cm 3 / g or more 2.0cm 3 / g or less, 0.8cm 3 / g or more 1.2cm 3 Less than / g, or 1.0cm 3 / g or more 1.2cm 3 It may be less than / g.
[0094] The separator (SS) may be, for example, a microporous membrane separator containing a polymer material (hereinafter also referred to as the base polymer). The base polymer may contain polyolefins. A polyolefin is a polymer containing at least olefin units (i.e., a polymer containing at least monomer units derived from olefins). Polyolefins and other base polymers may be used in combination as the base polymer. The ratio of polyolefins to the total base polymer contained in the separator is, for example, 50% by mass or more, may be 80% by mass or more, or may be 90% by mass or more. The ratio of polyolefins is, for example, 100% by mass or less. The base polymer may consist only of polyolefins.
[0095] Polyolefins include, for example, homopolymers of olefins, copolymers containing different olefin units, and copolymers containing olefin units and copolymerizable monomer units. Copolymers containing olefin units and copolymerizable monomer units may contain one or more types of olefin units. Copolymers containing olefin units and copolymerizable monomer units may also contain one or more types of copolymerizable monomer units. Copolymerizable monomer units are monomer units derived from polymerizable monomers other than olefins that are copolymerizable with olefins.
[0096] Examples of polyolefins include, for example, at least C 2-3 Examples include polymers containing olefins as monomer units. 2-3 Examples of olefins include at least one selected from the group consisting of ethylene and propylene. Examples of polyolefins include polyethylene, polypropylene, and C 2-3 Copolymers containing olefins as monomer units (e.g., ethylene-propylene copolymers) are more preferred. Among polyolefins, it is preferable to use polyolefins containing at least ethylene units (e.g., polyethylene, ethylene-propylene copolymers). Polyolefins containing ethylene units (e.g., polyethylene, ethylene-propylene copolymers) may be used in combination with other polyolefins.
[0097] Microporous film separators containing the above polymer material include crystalline regions where the base polymer molecules are relatively regularly arranged (i.e., highly aligned) and amorphous regions with low alignment. Therefore, in the XRD spectrum of the separator, diffraction peaks from the crystalline regions are observed, as well as scattered light from the amorphous regions, which is observed as a halo.
[0098] In the X-ray diffraction spectrum of the separator, the integrated intensity of the diffraction peak with the maximum peak height among the diffraction peaks corresponding to the crystalline region (the first diffraction peak) is defined as A1, and the integrated intensity of the halo peak attributed to the amorphous region is defined as A2. The ratio R expressed as A1 / (A1+A2) is defined as the degree of crystallinity. A degree of crystallinity R of 0.20 or higher is preferable. In this case, the degradation of the separator due to oxidation of the base polymer is suppressed, and a high lifetime performance is obtained.
[0099] The degree of crystallinity may be 0.20 or higher, and from the viewpoint of ensuring higher lifetime performance, it may be 0.23 or higher or 0.25 or higher. The degree of crystallinity may be 0.40 or lower, and may be 0.35 or lower or 0.30 or lower. When the degree of crystallinity is within this range, it is easier to ensure the flexibility of the separator and easier to manufacture.
[0100] The degree of crystallinity may be 0.20 or higher (or 0.23 or higher) and 0.40 or lower, 0.20 or higher (or 0.23 or higher) and 0.35 or lower, 0.20 or higher (or 0.23 or higher) and 0.30 or lower, 0.25 or higher and 0.40 or lower (or 0.35 or lower), or 0.25 or higher and 0.30 or lower.
[0101] For example, in the XRD spectrum of a separator containing polyolefins with ethylene units, diffraction peaks corresponding to the (110) plane in the crystalline region are observed in the range where 2θ is between 20° and 22.5°, and diffraction peaks corresponding to the (200) plane in the crystalline region are observed in the range where 2θ is between 23° and 24.5°. In addition, a halo in the amorphous region is observed in the range where 2θ is between 17° and 27°. Among the diffraction peaks due to the crystalline region, the diffraction peak corresponding to the (110) plane has the largest peak height and corresponds to the first diffraction peak.
[0102] The integrated intensities of the diffraction peak and halo are determined by fitting the diffraction peak from the crystalline region and the halo from the amorphous region to the XRD spectrum of the separator. The degree of crystallinity is then determined using the obtained integrated intensities A1 of the first diffraction peak and A2 of the halo.
[0103] A separator can be obtained, for example, by extruding a resin composition containing a base polymer, a pore-forming agent, and a penetrating agent (surfactant) into a sheet, stretching it, and then removing at least a portion of the pore-forming agent. Removing at least a portion of the pore-forming agent creates micropores in the matrix of the base polymer. The separator (or the resin composition used to produce the separator) may contain inorganic particles. After the removal of the pore-forming agent, the sheet-shaped separator is dried as needed. For example, the degree of crystallinity can be adjusted by adjusting at least one selected from the group consisting of the cooling rate of the sheet during extrusion, the stretching ratio during stretching, and the temperature during drying. For example, rapidly cooling the sheet during extrusion, increasing the stretching ratio, or lowering the temperature during drying tends to increase the degree of crystallinity. Stretching may be performed by biaxial stretching, but is usually performed by uniaxial stretching. The sheet-shaped separator may be folded into an accordion shape or processed into a bag shape as needed.
[0104] The pore structure and ratio r1 within the separator can be adjusted by adjusting the affinity between the base polymer and the pore-forming agent and / or penetrant, adjusting the dispersibility of the pore-forming agent, selecting the type and / or particle size of the inorganic particles, selecting the type of penetrant, adjusting the amount of inorganic particles, the amount of the pore-forming agent, and / or the amount of the penetrant, and / or adjusting the amount of functional groups and / or atoms present on the surface of the inorganic particles.
[0105] For separator analysis or size measurement, unused separators or separators removed from fully charged lead-acid batteries in their early stages of use are used. Separators removed from lead-acid batteries are washed and dried prior to analysis or measurement.
[0106] The separators removed from lead-acid batteries are cleaned and dried using the following procedure: The separators are immersed in pure water for 1 hour to remove sulfuric acid from them. Then, the separators are removed from the liquid and allowed to stand at 25°C ± 5°C for at least 16 hours to dry.
[0107] The XRD spectrum of the separator is measured by irradiating the separator surface with X-rays perpendicular to it. The sample for measurement is prepared by processing the portion of the separator facing the electrode material into a strip shape. For separators with ribs, the base portion is processed into a strip shape to avoid including the ribs. XRD spectrum measurement and fitting are performed under the following conditions. (Measurement conditions) Measurement device: RINT-TTR2, manufactured by Rigaku Corporation. Fitting: FT (Step Scan) method Measurement angle range: 15-35° Step width: 0.02° Measurement speed: 5° / min XRD data processing: XRD pattern analysis software (PDXL2, manufactured by Rigaku) was used.
[0108] The cumulative pore volume V1 and ratio r1 of the separator can be determined by using a mercury porosimeter to determine the pore distribution of a sample processed into a strip shape under the following conditions. Mercury porosimeter: Autopore IV9510, manufactured by Shimadzu Corporation. Measurement pressure range: 4 psia (≒27.6 kPa) to 60,000 psia (≒414 MPa) Pore size distribution: 0.01 μm to 50 μm
[0109] (electrolyte) The electrolyte is an aqueous solution containing sulfuric acid. The electrolyte may be gelled if necessary.
[0110] The electrolyte may further contain at least one metal ion selected from the group consisting of Na ions, Li ions, Mg ions, and Al ions.
[0111] The specific gravity of the electrolyte at 20°C is, for example, 1.10 or higher. The specific gravity of the electrolyte at 20°C may also be 1.35 or lower. These specific gravity values are for the electrolyte of a fully charged lead-acid battery (B).
[0112] The matters described herein can be combined in any way.
[0113] [Examples] The present invention will be described in detail below based on examples and comparative examples, but the present invention is not limited to the following examples. Here, a liquid lead-acid battery (B) with a nominal voltage of 12V and a 5-hour rate capacity of 30Ah was assembled. The 5-hour rate capacity is the capacity when discharged at a current (A) of 1 / 5 of the Ah value stated in the rated capacity.
[0114] [Evaluation Method] (1)HR discharge performance In accordance with the cold cranking current (CCA) test described in JIS D 5301:2019, the device is discharged for 30 seconds at -18°C ± 1°C using the rated cold cranking current, and the terminal voltage after discharge (voltage at 30 seconds of low-temperature HR discharge) (V) is determined. The HR discharge performance is evaluated based on this low-temperature HR discharge voltage at 30 seconds.
[0115] (2) Light load life test The battery life will be evaluated in accordance with JIS D5301:2019. Here, a fully charged lead-acid battery with a rated voltage of 12V will be repeatedly discharged and charged under the following conditions, and the number of cycles until it reaches the end of its life will be evaluated. Here, the discharge time for the light load life test will be set to 240 seconds to simulate a deep discharge cycle test.
[0116] In the light-load life test, the procedure is carried out according to (a) to (e) below, regardless of the difference in the 20-hour rate capacity of the test battery. Here, the 20-hour rate capacity is the capacity when discharged to the discharge termination voltage at a current (A) of 1 / 20 of the Ah value stated in the rated capacity. The steps (a) to (e) below are carried out in the gas phase at 75℃±2℃.
[0117] (a) Discharge: Discharge at a current of 25A for 240 seconds. (b) Charging: Charge at a constant voltage of 14.8V for 600 seconds (however, the maximum current is 100A). (c) Repeat: Repeat steps (a) and (b) above 480 times, with each step counting as one cycle. (d) Take a break for 40 to 60 hours. (e) Test discharge: After (d) above, discharge for 30 seconds at the rated cold cranking current Icc specified in JIS D5301:2019. The point at which the voltage drops to 7.2V 30 seconds after the start of discharge is considered the end of the life cycle, and the number of cycles until the end of the life cycle is defined as the life cycle count.
[0118] Since discharge with the rated cold cranking current Icc is performed every 480 cycles, the number of cycles at which the voltage at 30 seconds is 7.2V can be determined by linear interpolation from a graph with the voltage at 30 seconds in the Icc discharge on the vertical axis and the number of cycles on the horizontal axis, and this can be used as the life cycle count.
[0119] Examples 1-11, Comparative Examples 1-8 (Batteries E1~E11, Batteries C1~C8) Each lead-acid battery was manufactured using the following procedure. (1) Fabrication of separators A resin composition containing 100 parts by mass of polyethylene, approximately 160 parts by mass of silica particles, approximately 80 parts by mass of paraffin-based oil as a pore-forming agent, and 2 parts by mass of a penetrating agent was extruded into a sheet, stretched, and then a portion of the pore-forming agent was removed to produce a microporous membrane with ribs on one side. At this time, the amount of pore-forming agent removed was adjusted so that the cumulative pore volume V1 and ratio r1 of the separator, which were determined by the procedure described above, were the values shown in Table 1.
[0120] Next, a sheet-like microporous membrane was folded in half so that ribs were arranged on the outer surface to form a bag, and the overlapping ends were pressed together to obtain a bag-shaped separator.
[0121] (2) Fabrication of the positive electrode plate A positive electrode paste was prepared by mixing lead oxide, fibers, water, and sulfuric acid. The positive electrode paste was filled into the mesh of an expanded grid made of a Pb-Ca-Sn alloy, and aged and dried to obtain an unformed positive electrode plate with a width of 100 mm, a height of 110 mm, and a thickness of 1.6 mm.
[0122] The BET specific surface area and fiber diameter of the fibers used in the positive electrode paste are as shown in Table 1. The fibers were adjusted so that the fiber content relative to the total positive electrode material in a positive electrode plate taken from a fully charged lead-acid battery (B) was as shown in Table 1 by mass.
[0123] (3) Fabrication of the negative electrode plate A negative electrode paste was prepared by mixing lead oxide, carbon black, barium sulfate, lignin, water, and sulfuric acid. The negative electrode paste was filled into the mesh of an expanded grid made of a Pb-Ca-Sn alloy, which served as the negative electrode current collector. By aging and drying, an unformed negative electrode plate with a width of 100 mm, a height of 110 mm, and a thickness of 1.3 mm was obtained. The amounts of carbon black, barium sulfate, and lignin used were adjusted so that the content of each component in the negative electrode plate taken from a fully charged lead-acid battery (B) was 0.3 mass%, 2.1 mass%, and 0.1 mass%, respectively.
[0124] (4) Fabrication of lead-acid battery (B) The untreated negative electrode plates were placed in the bag-shaped separator prepared in (1), stacked with the positive electrode plates, and an electrode plate group was formed with 7 untreated negative electrode plates and 6 untreated positive electrode plates.
[0125] The tabs of the positive electrode plates and the tabs of the negative electrode plates were welded to the positive and negative electrode trays, respectively, using the cast-on-strap (COS) method. The six electrode plates were inserted into a polypropylene battery case, connected in series, and electrolyte was poured in. A chemical conversion was then performed inside the battery case to assemble a liquid lead-acid battery (B) with a nominal voltage of 12V and a 5-hour rate capacity of 30Ah.
[0126] A sulfuric acid solution was used as the electrolyte. The specific gravity of the electrolyte after chemical conversion was 1.285 at 20°C.
[0127] (5) Evaluation The obtained lead-acid battery (B) was evaluated by performing HR discharge performance and light load life tests according to the procedure described above. The evaluation results are shown in Table 1. In Table 1, the evaluation results for HR discharge performance and light load life tests are shown as relative values with comparative example battery C2 set to 100.
[0128] [Table 1]
[0129] From Table 1, the cumulative pore volume V1 is 0.8 cm³. 3 / g or more 2.0cm 3 A separator (SS) is used that is less than / g and has a ratio r1 of 50% or more, and the BET specific surface area of the fibers contained in the positive electrode material is 0.3m². 2 / g or more 1.0m 2 In lead-acid batteries (B) with a range of less than / g, we were able to achieve both long lifespan and high HR discharge performance.
[0130] Without using a separator (SS), the cumulative pore volume V1 is 0.8 cm³. 3 Batteries C1 and C2, with a refractometer ratio of less than 50% and a ratio of less than 50%, exhibit a long light-load lifespan and do not experience the problem of softened and detached positive electrode material penetrating the pores of the separator, thus ending their lifespan. On the other hand, batteries C1 and C2 have low HR discharge performance.
[0131] A comparison of batteries C1 to C6 shows that as V1 and / or r1 increase, the light-load life decreases, but the HR discharge performance tends to improve. In C3 to C5, the decrease in light-load life performance due to the use of separators (SS) is significant. In contrast, the BET specific surface area of the fibers is 0.3m². 2 By setting the value to 1 / g or higher, we were able to achieve high HR discharge performance while maintaining high light-load life performance, as shown in batteries E1 to E3.
[0132] From a comparison of batteries E1, E4, E5, C3, and C7, when using a separator (SS), the BET specific surface area of the fiber is 0.3 m². 2 / g or more 1.0m 2 It was confirmed that high light-load lifespan performance and high HR discharge performance can be achieved simultaneously in the range of less than / g. Furthermore, from a comparison of batteries E1, E6, E7, and C8, it was confirmed that high light-load lifespan performance and high HR discharge performance can be achieved simultaneously when the separator (SS) ratio r1 is between 50% and 70%. In addition, from a comparison of batteries E1, E8 to E11, the effect of achieving both high light-load lifespan performance and high HR discharge performance was greater when the fiber content was between 0.07 mass% and 0.2 mass%. [Industrial applicability]
[0133] The lead-acid battery according to this disclosure is suitable, for example, as a lead-acid battery for vehicles employing a start-stop system, and can also be suitably used as a power source for industrial energy storage devices such as electric vehicles (forklifts, etc.). These applications are merely examples. The applications of the lead-acid battery according to the present invention are not limited to these. [Explanation of Symbols]
[0134] 1: Lead-acid battery, 2: Negative electrode plate, 3: Positive electrode plate, 4: Separator, 5: Positive electrode shelf, 6: Negative electrode shelf, 7: Positive electrode column, 8: Through connector, 9: Negative electrode column, 11: Electrode plate group, 12: Battery case, 13: Partition wall, 14: Cell chamber, 15: Cover, 16: Negative electrode terminal, 17: Positive electrode terminal, 18: Electrode cap
Claims
1. It comprises a positive electrode plate, a negative electrode plate, an electrolyte, and a separator interposed between the positive electrode plate and the negative electrode plate. The positive electrode plate includes a positive electrode current collector and a positive electrode material. The positive electrode material includes fibers, The aforementioned fiber has a BET specific surface area of 0.3 m², measured using krypton gas as the adsorbent gas. 2 / g or more 1.0m 2 / g or less, In the pore size distribution of the separator, the cumulative pore volume V1 of pores with diameters from 0.005 μm to 10 μm is 0.8 cm³. 3 / g or more 2.0cm 3 / g or less, A lead-acid battery in which the ratio r1 of the pore volume V2 with a pore diameter of 0.1 μm or more and 10 μm or less to the total pore volume V1 is 50% or more.
2. The lead-acid battery according to claim 1, wherein the fiber content in the positive electrode material is 0.01% by mass to 0.23% by mass.
3. The lead-acid battery according to claim 1, wherein the average fiber diameter of the aforementioned fibers is 10 μm or less.
4. The lead-acid battery according to claim 1, wherein the average fiber diameter of the aforementioned fibers is 1 μm to 8 μm.
5. The surface of the aforementioned fiber has irregularities, The lead-acid battery according to any one of claims 1 to 4, wherein the irregularities are formed along the circumferential direction of the fibers.
Citation Information
Patent Citations
Lead storage battery
JP2019067741A
Improved separator for reinforced flooded batteries, batteries, and related methods
JP2019514173A